Analisis Tren Penelitian Sambungan Baut dan Las pada Baja H-Beam Menggunakan Pendekatan Bibliometrik - Bulan suryani; Dwi widya putri; Fathir achmad; Sadan Habib (Lembaga Pengembangan Kinerja Dosen, 2026)
Research on bolted and welded connections in H-beam steel structures has continued to grow due to the increasing demand for strong, efficient, and earthquake-resistant steel structures. This study aims to analyze publication trends, researcher collaboration patterns, and thematic developments related to bolted and welded connections using a bibliometric approach. The data were obtained from the Scopus database consisting of 302 publications from 2019 to 2025. The analysis was conducted using Bibliometrix in RStudio and visualized using VOSviewer. The results show that the number of publications increased significantly each year, indicating growing research interest in steel connection studies. Keyword analysis revealed that the dominant topics include bolted connections, finite element methods, seismic design, and structural health monitoring. The thematic mapping indicates that stiffness, energy dissipation, and structural performance are the main research focuses. In addition, co-authorship analysis demonstrates active scientific collaboration among researchers in the development of steel connection studies. Overall, research on bolted and welded connections in H-beam steel structures is developing toward a multidisciplinary approach integrating numerical analysis, structural performance evaluation, and modern monitoring technology.